2016
DOI: 10.1001/jamaoncol.2016.0241
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Therapy for Advanced Soft-Tissue Sarcomas in Adults

Abstract: The biological features of each sarcoma subtype are associated with specific sensitivity patterns to chemotherapy, and despite their rarity, future trials will need to emphasize specific histologic subtypes (many with well-defined genetic alterations) to best fit diagnosis to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Patients with metastatic soft tissue sarcomas generally have a poor prognosis, with low response rates after first line chemotherapy [3]. Of note, the tyrosine kinase inhibitor pazopanib was approved by the FDA in 2012 on the basis of a phase III randomized trial showing improved PFS in the second line setting; the overall response rate was only 6% [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with metastatic soft tissue sarcomas generally have a poor prognosis, with low response rates after first line chemotherapy [3]. Of note, the tyrosine kinase inhibitor pazopanib was approved by the FDA in 2012 on the basis of a phase III randomized trial showing improved PFS in the second line setting; the overall response rate was only 6% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Despite new studies elucidating the genomic basis and the sensitivity to chemotherapy of specific subtypes, the overall prognosis of patients with metastatic sarcoma remains poor in most cases. Since 2012, new drugs such as pazopanib, and for more specific subtypes, trabectedin and eribulin, have been approved for patients who have relapsed after front line chemotherapy, but the response rates for these agents remains suboptimal [3]. Immunotherapy has recently provoked great interest in oncology after phase III clinical trials have shown significant efficacy in chemotherapy-resistant malignancies such as metastatic melanoma or renal cell carcinoma, and activity in chemotherapy-sensitive histologies including non-small cell lung cancer, head and neck cancer, MSI-high colon cancer and Hodgkin’s lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Our work strongly implicates Rb as a biomarker for CDK4/6 inhibitor combinations, similar to data from other cancer types such as breast cancer and glioblastoma. Selection for enrollment based on biomarkers is more likely to be successful versus the standard approach of enrollment by histologic criteria alone (39). The frequency of Rb positivity within sarcoma appears to differ among histologic subtypes, and not be universally expressed in any subtype.…”
Section: Discussionmentioning
confidence: 99%
“…2 Conventional chemotherapy benefits patients with advanced STS with objective response rates from 15 to 25% with drugs such as doxorubicin, ifosfamide, and dacarbazine. A current paradigm shift favors pathological subtype-specific chemotherapy regimen, 3 and recent drug approvals were linked with specific sarcoma subtypes, such as trabectedin for leiomyosarcomas and liposarcomas, first described in sarcoma patients, whose tumor regressed after an infection 10 or after local injections of streptococcal broth cultures. 11 Similar to melanoma or kidney cancer, cases of spontaneous regression were reported in patients with sarcoma.…”
Section: Introductionmentioning
confidence: 99%